PENDIDIKAN PEMUSTAKA UNTUK MENCERDASAN PEMUSTAKA - Nurhayati Zein (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2017)
Abstract: College libraries are the heart of universities. This statement has become a commitment for all academicians, but this statement has not been fully enforced by each related party. Like the level of use of library collections, both for library users among the teaching staff (lecturers), students or researchers, even for librarians themselves are those who consider collections that are not touched by users because they are difficult to read, just be put away to the warehouse, in the case that the collections contain information that is of scientific value that is straight, worthy of being used as a scientific benchmark. The visit to the library has decreased, because the user feels unable to read various kinds of information that are already available in the library. Therefore, it is necessary to support user education activities as the main task of the librarian.Keywords: Librarian, Librarian and User EducationAbstrak : Perpustakaan perguruan tinggi adalah jantungnya perguruan tinggi . pernyataan ini sudah menjadi komitmen bagi semua civitas academika,akan tetapi pernyataan ini belum sepenuhnya diberlakukan oleh masing masing pihak terkait.seperti tingkat keterpakaian koleksi perpustakaan, baik itu bagi pemustaka dari kalangan tenaga pengajar ( dosen ), kalangan mahasiswa ataupun dari kalangan peneliti ,bahkan bagi pustakawan itu sendiri ada yang menganggap koleksi koleksi  yang kurang dijamah oleh pemustaka karena sulit dibaca disingkirkan saja ke gudang,pada hal koleksi tersebut berisi informasi  yang bernilai ilmiah yang lurus,pantas dijadikan tolok ukur ilmiah. Kunjungan ke perpustakaan menjadi menurun , karena pemustaka merasa tidak mampu membaca bermacam macam  informasi yang sudah tersedia di perpustakaan.Oleh sebab itu perlu didukung kegiatan  user education  sebagai tugas pokok pustakawan.Kata kunci : Pemustaka, Pustakawan dan User Education